Reconnecting a fragmented landscape: a multi-scale ecological approach to green space design in Wichita, Kansas - Parker, Caleb (Kansas State University, 2020)
As the impact of urbanization is felt more and more in cities around the world the preservation of nature has become less of a priority. This has led to a lack of nature in many urban cities which is causing many social and environmental problems. One of the main issues is the high degree of fragmentation that is occurring in cities, which disrupts natural processes and creates unequal access to nature for the city’s residents. The City of Wichita, Kansas is currently experiencing some of these problems due to its sprawling development patterns. The study objectives were: (a) to contribute to the development of a multi-scale ecological design approach that links spatial landscape analysis and ecological site-design modeling; and, (b) to reconnect fragmented landscapes by reclaiming and redistributing urban green spaces as social and ecological assets in Wichita, Kansas. This objective was accomplished through a two-phase process. The first phase focused on a city-level analysis. In this phase GIS and FRAGSTATS were used in combination to identify different patterns within the fragmented landscape. Solutions and suggestions were then made for each of the types of fragmentation that were found to be occurring. Following this analysis, one of the most fragmented sites was chosen. In the second phase, the selected site was then analyzed to determine which type or types of fragmentation were occurring. Using the typological solutions generated in phase one, a site design was developed to demonstrate how the higher-level ideas in phase one can be applied at the site level. This project serves as an example of how landscape architects can use a more data-driven method to design green space in an urban context, such as landscape pattern analysis techniques which allows them to collaborate with other professionals more effectively.
Keywords: Wichita, Kansas; Landscape Fragmentation; FRAGSTATS